1995
DOI: 10.1155/dte.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography‐Guided Bronchoscopy With an Ultrathin Fiberscope

Abstract: Bronchoscopy was performed under computed tomography (CT) guidance using an ultrathin fiberscope in a patient with a fluoroscopically invisible lesion that was visualized by CT in the right S and with poor pulmonary function. Under local anesthesia, the ultrathin fiberscope (3 mm in diameter) was inserted close to the lesion (1.5 mm in diameter) under direct visual guidance, and a brush was inserted into the lesion under CT guidance. Cytologic specimens obtained by the brush and washing revealed adenocarcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 2 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…The marking technique essentially entails the installation of a barium-sulfate suspension near lesions that are not detectable fluoroscopically or thorascopically. 9,10 A final issue covers the determination of standardized treatments for CT-detected lesions. Current practice dictates the performance of a lobectomy for patients with these lesions based on the unacceptably high rates of disease recurrence in patients with incompletely resected tumors.…”
Section: Ct Screening: Problems and Solutionsmentioning
confidence: 99%
“…The marking technique essentially entails the installation of a barium-sulfate suspension near lesions that are not detectable fluoroscopically or thorascopically. 9,10 A final issue covers the determination of standardized treatments for CT-detected lesions. Current practice dictates the performance of a lobectomy for patients with these lesions based on the unacceptably high rates of disease recurrence in patients with incompletely resected tumors.…”
Section: Ct Screening: Problems and Solutionsmentioning
confidence: 99%
“…To make use of this advantage, we have proposed a method in which a bronchoscope is navigated using virtual bronchoscopic images en route to the lesion (virtual bronchoscopic navigation: VBN) (11). For a method that combines measures addressing the two abovementioned problems stated, Kobayashi et al reported CTguided ultrathin bronchoscopy (12). Using the combination of ultrathin bronchoscopy and CT, the position of the biopsy apparatus at the lesion can be more accurately confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons for this result is that small lesions cannot be confirmed by X-ray fluoroscopy alone, and it cannot be confirmed whether biopsy forceps or a brush accurately hit the lesion. To overcome this problem, CT fluoroscopy [11,12], endobronchial ultrasonography (EBUS) [13,14], and the electromagnetic method [15,16] have been used to confirm lesions diagnosed by TBB. EBUS is advantageous over the other methods because of the absence of X-ray exposure and because there is no need for expensive equipment other than an ultrasonography system.…”
Section: Introductionmentioning
confidence: 99%